2019
DOI: 10.3390/insects10110394
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Transmission of Deformed Wing Virus to Ants (Myrmica rubra)

Abstract: Virus host shifts occur frequently, but the whole range of host species and the actual transmission pathways are often poorly understood. Deformed wing virus (DWV), an RNA virus described from honeybees (Apis mellifera), has been shown to have a broad host range. Since ants are often scavenging on dead honeybees, foodborne transmission of these viruses may occur. However, the role of the ant Myrmica rubra as an alternative host is not known and foodborne transmission to ants has not been experimentally address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 67 publications
(131 reference statements)
3
28
0
Order By: Relevance
“…However, none of these samples tested positive for replication of DWV, BQCV, or IAPV. Overall, previous studies have tested only a relatively few number of ant species for the replication of DWV, BQCV, or IAPV [21][22][23]27 . Argentine ants are one of the few ant species that have been tested for a honey bee-associated virus (DWV) in multiple areas worldwide including Argentina, New Zealand, Australia, and now the United States.…”
Section: Number Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of these samples tested positive for replication of DWV, BQCV, or IAPV. Overall, previous studies have tested only a relatively few number of ant species for the replication of DWV, BQCV, or IAPV [21][22][23]27 . Argentine ants are one of the few ant species that have been tested for a honey bee-associated virus (DWV) in multiple areas worldwide including Argentina, New Zealand, Australia, and now the United States.…”
Section: Number Of Samplesmentioning
confidence: 99%
“…This is especially likely of ants that are common pests within hives, such as S. invicta and Crematogaster sp. For instance, a previous study showed that ants can acquire honey bee-associated viruses through foodborne transmission (i.e., the ingestion of infected honey bee pupae) 27 . However, further research looking at the possible transmission mechanisms of these viruses from ants to honey bees is needed to determine whether or not ants play a role in transmitting viruses to honey bees, which would contribute to the declining health of this important pollinator.…”
Section: Number Of Samplesmentioning
confidence: 99%
“…Yet, new research suggests that DWV may not replicate in mite cells but in honey bee cells recently consumed by mites [78]. Nevertheless, feeding experiments have shown that scavenger species like the ant Myrmica rubra are found positive for the negative strand of DWV for up to 13 weeks after consuming infected honey bees [14], which indicates that DWV actively infects ants. Whether honey bee scavengers are able to spread viruses without becoming infected themselves [79] or aid in reducing virus transmission by removing infectious carcasses [80] remains to be tested.…”
Section: Multi-host Viruses In Emerging Diseasementioning
confidence: 99%
“…Viral infections have been extensively studied in the European honey bee (Apis mellifera) because a number of RNA viruses that are circulating within bee populations have been associated with reduced health and reports of colony collapses [8,9]. Increasing evidence suggests that many of these pathogens are not specific to honey bees and instead are shared between many pollinator species and associated arthropods, including bumble bees and other wild bees [10][11][12]; bee predators, such as wasps [10,11]; and scavenging insects, such as ants, cockroaches, and beetles [10,[13][14][15]. Many of these host species have been found cohabiting in bee hives [13,15,16] or share floral resources with honey bees [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The identified transmission routes for honey bee viruses include horizontal pathways, such as vector-borne transfer by parasitic mites, foodborne-, venereal-and faecal-oral transmission, as well as vertical transmission from the queens to their eggs [21]. Although foodborne transmission seems to be less effective in honey bees, it may nevertheless be a crucial pathway for the infection of other species [22], especially predators and scavengers [23,24]. However, at present, there are little data on the actual impact of honey bee-derived viruses on alternative hosts.…”
Section: Introductionmentioning
confidence: 99%